Improving crest factor of electronic ballast-fed fluorescent lamp current using pulse frequency modulation - Song, J; Song, JH; Choy, I; Choi, JY (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2001)
In case where electronic ballast employing a valley-fill passive power-factor correction (PFC) circuit is used for feeding fluorescent lamps, a new method to reduce crest factor of the lamp current is studied in this paper. It is known that a 50% valley-fill passive PFC provided for high input power factor results in undesirable value of crest factor of the fluorescent lamp current. In order to reduce crest factor to a lower value, a pulse frequency modulation technique based on the waveform of the dc-link voltage which is predetermined by the passive PFC circuit is taken into the switching control action of the electronic ballast. An equation-based analysis between the crest factor of lamp current and the effect of varying the inverter switching frequency is comprehensively performed. Several simulation and experiment results illustrate the effectiveness of the proposed control scheme.
Keywords: INVERTER; DESIGN; MODEL